Modelling adiabatic shear banding via damage mechanics approach (Archives of Mechanics - Test, 2003)
During dynamic loading processes, large plastic deformation assiciated with high strain rates leads, for a broad class of ductile materials, to degradation and failure by adiabatic shear banding. The paper presents an attempt to model some salient features of this process viewed as an anisotropic damage mechanism coupled with thermo-elastic/viscoplastic deformation. The model is destined to be applied in the context of high velocity impact and penetration mechanics. The methodology employed within the framework of the internal state variable structure strives to keep a middle way between extensive description of complex viscoplastic flow and damage events and application-oriented accessibility requirements. Model capabilities are prelaminarly illustrated for shear loading process.